Latent profiles of sleep quality, financial management behaviors, and sexual satisfaction in emerging adult newlywed couples and longitudinal connections with marital satisfaction - Saxey, Matthew T.; Li, Xiaomin; Wikle, Jocelyn S.; Hill, E. Jeffrey; LeBaron-Black, Ashley B.; James, Spencer L.; Brown-Hamlett, Jessica L.; Holmes, Erin K.; Yorgason, Jeremy B. (Frontiers in Psychology, 2022)
Emerging adult newlywed couples often experience many demands on their time, and three common problems may surface as couples try to balance these demands—problems related to finances, sleep, and sex. We used two waves of dyadic data from 1,001 emerging adult newlywed couples to identify four dyadic latent profiles from husbands’ and wives’ financial management behaviors, sexual satisfaction, and sleep quality: Flounderers, Financially Challenged Lovers, Drowsy Budgeters, and Flourishers. We then examined how husbands’ and wives’ marital satisfaction, in relation to profile membership, varied at a later wave. We found that Financially Challenged Lovers and Flourishers had significantly higher marital satisfaction than Drowsy Budgeters and Flounderers (mostly medium effect sizes). Whereas, Financially Challenged Lovers and Flourishers did not differ in terms of marital satisfaction, Drowsy Budgeters seemed to have slightly higher marital satisfaction than Flounderers for wives only (small effect size). However, we did not find evidence that these connections meaningfully differed by sex. Implications for the efforts of clinicians and educators are discussed.